2016
DOI: 10.1007/s00404-016-4188-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and pregnancy outcomes of Syrian refugees: a case–control study in a tertiary care hospital in Istanbul, Turkey

Abstract: In comparison to non-refugee control patients, refugee women in our study had poor antenatal care but no adverse perinatal outcomes were observed. Further larger multicenter studies may provide more convincing data about obstetric outcomes in the Syrian refugee population as well as adolescent pregnancies in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
72
6
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 20 publications
16
72
6
12
Order By: Relevance
“…A comparison of local Turkish women and Syrian refugee women in terms of the presence of prenatal anemia revealed no significant difference in Hb and Hct values, and nor was there any significant difference in terms of the obstetric complications of thromboembolism, infection, and atony. Previous studies have recorded poor pregnancy outcomes in the majority of refugee women, with fetal distress, preterm delivery, gestational diabetes mellitus, a higher rate of cesarean delivery, intrauterine fetal demise, neonates with low Apgar scores, and an increased need for admission to the NICU being among the increased risks . The government of the Republic of Turkey offers free health care to Syrian refugees and facilitates their access to healthcare resources.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of local Turkish women and Syrian refugee women in terms of the presence of prenatal anemia revealed no significant difference in Hb and Hct values, and nor was there any significant difference in terms of the obstetric complications of thromboembolism, infection, and atony. Previous studies have recorded poor pregnancy outcomes in the majority of refugee women, with fetal distress, preterm delivery, gestational diabetes mellitus, a higher rate of cesarean delivery, intrauterine fetal demise, neonates with low Apgar scores, and an increased need for admission to the NICU being among the increased risks . The government of the Republic of Turkey offers free health care to Syrian refugees and facilitates their access to healthcare resources.…”
Section: Discussionmentioning
confidence: 99%
“…They are screened for infectious and non‐infectious diseases and receive vaccinations, and women with high‐risk pregnancies are referred to hospitals . However, most Syrian refugees have not been registered with family physicians yet, instead undergoing health checks in community health centers . In Lebanon, it has been shown that the prenatal monitoring requirements of Syrian refugees are not being met, so it is likely that prenatal monitoring of female refugees in Bursa is disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Our results were in conformity with other similar studies done by Lalita Bahl et al, A.S.M Iqbal et al, Jeswani and Vani et al, Elizabeth et al The researchers in their study found a similar association between cord blood, levels of zinc and low birth weight. 7,8 The results of present study show, Low serum zinc is a significant predictor of low birth weight, if the results are replicable, they will have important implications for both the prediction of low birth weight and possibly the prevention of low birth weight.…”
Section: Discussionmentioning
confidence: 58%
“…Majority of these studies were performed in developed countries. [7][8][9][10] Unlike in developed countries, where preterm is the main cause of low birth weight, in developing countries most low birth weight infants are small for gestational age. Low zinc concentrations in the cord blood of low birth weight newborns have been noted in a number of settings and birth weight has been shown to be highly correlated with cord zinc concentration.…”
Section: Introductionmentioning
confidence: 99%